Detection of Bacillus anthracis in animal tissues using InBios active anthrax detect rapid test lateral flow immunoassay. (28th March 2019) - Kolton, C.B.; Marston, C.K.; Stoddard, R.A.; Cossaboom, C.; Salzer, J.S.; Kozel, T.R.; Gates‐Hollingsworth, M.A.; Cleveland, C.A.; Thompson, A.T.; Dalton, M.F.; Yabsley, M.J.; Hoffmaster, A.R.
Abstract: The Active Anthrax Detect (AAD) Rapid Test lateral flow immunoassay is a point‐of‐care assay that was under investigational use for detecting Bacillus anthracis capsular polypeptide (polyglutamic acid) in human blood, serum and plasma. Small sample volumes, rapid results and no refrigeration required allow for easy use in either the field or laboratory. Although the test was developed for use in suspect cases of human inhalation anthrax, its features also make it a potentially powerful tool for testing suspect animal cases. We tested animal tissue samples that were confirmed or ruled out for B. anthracis . The AAD Rapid Tests were also deployed in the field, testing animal carcasses during an anthrax outbreak in hippopotami ( Hippopotamus amphibius ) and Cape buffalo ( Syncerus caffer ) in Namibia. Evaluation of all samples showed a specificity of 82% and sensitivity of 98%. However, when the assay was used on specimens from only fresh carcasses (dead for <24 h), the specificity increased to 96%. The AAD Rapid Test is a rapid and simple screening assay, but confirmatory testing needs to be done, especially when the age of the sample (days animal has been deceased) is unknown. Significance and Impact of the Study: In countries where anthrax is endemic, many human outbreaks are often caused by epizootics. Earlier detection of infected animals may allow for identification of exposed people, early implementation of prevention and control methods, and ultimately lessen the number of people and animals affected. Detection of Bacillus anthracis in animal tissues using a simple, rapid and field‐deployable method would allow for faster outbreak response. We evaluated a simple sample collection and processing method for use with the Active Anthrax Detect Rapid Test lateral flow immunoassay to screen dead animals for anthrax. Abstract : Significance and Impact of the Study In countries where anthrax is endemic, many human outbreaks are often caused by epizootics. Earlier detection of infected animals may allow for identification of exposed people, early implementation of prevention and control methods, and ultimately lessen the number of people and animals affected. Detection of Bacillus anthracis in animal tissues using a simple, rapid and field‐deployable method would allow for faster outbreak response. We evaluated a simple sample collection and processing method for use with the Active Anthrax Detect Rapid Test lateral flow immunoassay to screen dead animals for anthrax.